Accuracy of home blood pressure measurement: the ACCURAPRESS study – a proposal of Young Investigator Group of the Italian Hypertension Society (Società Italiana dell'Ipertensione Arteriosa). (31st December 2022) - Mancusi, Costantino; Bisogni, Valeria; Maloberti, Alessandro; Manzi, Maria Virginia; Visco, Valeria; Biolcati, Marco; Giani, Valentina; Spannella, Francesco; Monticone, Silvia; Saladini, Francesca; Rivasi, Giulia; Turrin, Giada; et al.
Abstract: Purpose: Home blood pressure monitoring (HBPM) might be considered a valid alternative to ambulatory blood pressure monitoring (ABPM) for both the diagnosis and management of hypertension. Correct information on how to perform HBPM are crucial for its reliability. The aim of the present survey was to assess if hypertensive patients followed current recommendation on how to correctly perform HBPM measurements. Materials and methods: The survey included 30 different items on how to perform the HBPM. It was developed by the 'Young Investigators' group of the Italian Society of Arterial Hypertension (SIIA) and it was administered during the office visit between May 2019 and December 2021. Results: A total of 643 hypertensive patients participated in the study. Main results show that, despite the rate of informed patients was relatively high (71% of the whole population), unacceptable number of patients did not follow indications on how to perform a correct HBPM. Patients who were informed on how to measure home BP had a significantly higher rate of correct position during measurement (78 vs. 22%, p < 0.01), avoidance of talking and moving during measurement (68 vs. 32%, p < 0.0001), and correct number and time interval between two measurements (85 vs. 15%, p < 0.001). More accurate measurements of home BP were associated with less prevalence of carotid plaque. Conclusions: Correct performance for HBPM is low among patients treated in Italian hypertension centers. These findings shed light on the importance of correct HBPM measurements for the detection of accurate BP values for the proper management of hypertensive patients.